Addressing competency gaps for vocational instructor through competency modelling - Arifin, Muhammad Aiman; Mohd Rasdi, Roziah; Mohd Anuar, Mohd Ashraff; Omar, Muhd Khaizer (Human Resource Management Academic Research Society, 2017)
The purpose of this paper is to comprehend the competency and competency models at workplace settings, its significance to human resource development in terms of knowledge, skills and abilities. In the management literature, the competency based approach has grown through McClelland (1973) seminal paper “testing for competencies rather than intelligence” as to argue the traditional approach to measure performance using aptitude and content test. Evidence had also indicated that competency can lead to effective job performance. The practice of competency base approach has resulted with the expansion of term, models of specific profession also the application. This paper discusses the previous competency literature with greater interest on the field of competency, competency models and technical vocational education and training in Malaysia specific for vocational teaching profession. This study suggests that competency modelling can contribute to the effectiveness of vocational teacher education and to address competency gaps issues. Competency modelling for vocational teaching is still is in its infancy however the lack of competent teachers is a challenge for Malaysia to reach a better income levels in future.